2022
DOI: 10.3991/ijet.v17i04.22563
|View full text |Cite
|
Sign up to set email alerts
|

Distance Education: An Investigation of Tutors’ Electronic Feedback Practices during Coronavirus Pandemic

Abstract: The current study investigated the patterns of English language tutors’ e-feedback practices during the coronavirus pandemic, learners’ response to tutors’ e- feedback and the important issues that emerged from e-feedback practices. Quantitative and qualitative analysis of the online questionnaire and the semi-structured interviews were performed. The findings indicate that (1) English language tutors concentrate slightly more on local issues than global issues, provide eight main types of e-feedback; clarific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Unlike in the past decades, students can study and attend classes and courses via online teaching and learning platforms internationally. Besides international students, non-traditional, evening, returning, and adult students also enjoy the flexibility of the online teaching and learning platform due to the development of technology (Olesen-Tracey, 2010;AbuSa'aleek and Alotaibi, 2022). The current online learning experience provided this unique opportunity as the online platform connected students inside and outside the country, thus appropriately meeting students' motivations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike in the past decades, students can study and attend classes and courses via online teaching and learning platforms internationally. Besides international students, non-traditional, evening, returning, and adult students also enjoy the flexibility of the online teaching and learning platform due to the development of technology (Olesen-Tracey, 2010;AbuSa'aleek and Alotaibi, 2022). The current online learning experience provided this unique opportunity as the online platform connected students inside and outside the country, thus appropriately meeting students' motivations.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study (Dos Santos, 2021d) also indicated that domestic and international students enjoyed the online learning environment as many could continue their education, particularly during the lockdown and COVID-19 pandemic. The participants indicated that the online learning options should be continued to meet the needs of students from different background (Atmojo and Nugroho, 2020;AbuSa'aleek and Alotaibi, 2022;Chen and Du, 2022).…”
Section: Motivation and Reason Of Online Learningmentioning
confidence: 99%
“…International Journal of Instruction, January 2024 • Vol.17, No.1 teaching to online learning platforms and environments (AbuSa'aleek & Alotaibi, 2022). As both K-12 and university classes needed to be taught from online platforms, university departments needed to arrange online-based student-teaching internships as no physical classrooms were available in on-campus environments (Moorhouse, 2020;Stewart & Lowenthal, 2022).…”
Section: Experiences and Sense-making Processes Of Online Teaching …mentioning
confidence: 99%
“…To describe the underlying theories of giving feedback, behavioral learning theory (Skinner, 2011) was another theory that served as the basis for this study. Feedback was initially believed to be associated with the behaviorist approach, which views writing instruction as a series of stimuli delivered by the teacher and the student's responses to these stimuli (Gezahegn & Gedamu, 2023;AbuSa'aleek & Alotaibi, 2022;AbuSa'aleek & Shariq,2021).…”
Section: Introductionmentioning
confidence: 99%